Synergistic Combination of Chitosan and Cinnamid Acid as Edible Coating to Extend Self-life of Acelora Cherry (Malpighia emarginata) Fruit - N. P. Minh (Journal of Global Pharma Technology, 2019)
Chitosan is edible coating which is a safe, biodegradable and non-toxic substance derived from chitin shells of crustaceans. It’s considered as an antifungal agent that can control postharvest diseases. Cinnamic acid is a plant-derived soluble compound that impedes microbial growth. Acerola cherry (Malpighia emarginata) fruit is well known as one of the richest natural sources of ascorbic acid as well as its high concentration of health-relevant phytochemicals. It has a red color and highly perishable at complete maturity, resulting in serious quality losses during post-harvest. Purpose of this research demonstrated the efficacy of chitosan combined with cinnamid acid as edible coating to extend self-life of acelora cherry fruit. Finding results revealed that chitosan 1.5% + 2 mM cinnamid acid was appropriate to limit weight loss; maintain firmness, chlorophyll, and vitamin C content effectively. Microbial safety was also monitored on treated samples during 8 days of storage at ambient temperature. The combination of chitosan and cinnamic acid provides synergistic effect as a semi-permeable barrier to delay the respiration rate.Keywords: Acelora cherry, Chitosan, Cinnamid acid, Coating, Weight loss, Firmness, Chlorophyll, vitamin C.